2009
DOI: 10.1136/gut.2008.171280
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of non-alcoholic fatty liver disease in children: a follow-up study for up to 20 years

Abstract: Objectives: The long-term prognosis of non-alcoholic fatty liver disease (NAFLD) in children remains uncertain. We aimed at determining the long-term outcomes and survival of children with NAFLD. Design: Retrospective longitudinal hospital-based cohort study. Patients: Sixty-six children with NAFLD (mean age 13.9 (SD 3.9) years) were followed up for up to 20 years with a total of 409.6 person-years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
459
1
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 634 publications
(481 citation statements)
references
References 45 publications
10
459
1
11
Order By: Relevance
“…While most authorities agree that steatosis alone is not a risk for progressive liver disease, in fact, published series have shown progressive fibrosis in a small number of patients over several years of follow-up [29,30]. A 20-year pediatric natural history study utilizing liver biopsy has confirmed the risk of cirrhosis as well as recurrence of NAFLD in the transplanted liver in affected children [31]. …”
Section: Liver Biopsy Evaluation In Clinical Investigation: Prevalencmentioning
confidence: 99%
“…While most authorities agree that steatosis alone is not a risk for progressive liver disease, in fact, published series have shown progressive fibrosis in a small number of patients over several years of follow-up [29,30]. A 20-year pediatric natural history study utilizing liver biopsy has confirmed the risk of cirrhosis as well as recurrence of NAFLD in the transplanted liver in affected children [31]. …”
Section: Liver Biopsy Evaluation In Clinical Investigation: Prevalencmentioning
confidence: 99%
“…Limited data suggests that children diagnosed with NAFLD have increased morbidity and mortality rates in adulthood (9). NASH can cause severe complications such as cirrhosis (1).…”
Section: Nafldmentioning
confidence: 99%
“…Indeed, it is now largely accepted that NAFLD represents the hepatic features of the metabolic syndrome and is associated with increased mortality [5,6]. …”
Section: Introductionmentioning
confidence: 99%